China’s Academic Profession Hit by “Involution” - Zha, Qiang (International Higher Education, 2021)
China’s robust production of research publications has not translated into innovation, and the country is riddled with key technology bottlenecks amid the US-China trade war. A situation of “involution” has been cited as a responsible factor for this paradox. When translated into the academic profession, “involution” refers to a situation whereby most university-based researchers work harder and publish more papers, while the innovative strength of Chinese higher education does not grow significantly.